Uang Ces: Trust Sawi Terhadap Punggawa Pada Komunitas Nelayan Sumpang Binangae Kabupaten Barru - Ulfa Utami Mappe; Idham Irwansyah Idrus (Jurnal Neo Societal, 2024)
This study aims to identify the trust between sawi fishermen and punggawa in the fishing community in Sumpang Binangae Sub District, Barru Districty. Data collection was carried out using a qualitative descriptive method. Data analyzed through three stages; 1) data reduction, 2) data presentation, 3) drawing conclusion and verification.  The results of the study show; trust as the most important part to maintaining the working relationship between sawi fishermen and punggawa. The distribution of the catch sharing is divided into four forms; distribution every one to eight months, pakanreang fish, ces money, and the cost of excess maintenance of bagang lights called lamp percent. For Sawi fishermen, ces money as the main income to meet the daily needs of family. This is because the distribution of monthly sales is uncertain. Through profit sharing, norms and values are internalized by everyone in the Sumpang Binangae fishing community.The values and norms, results trust. The conclusion of this research is the resulting form of trust can be either high-trust or low-trust. High-trust or low-trust is characterized by the time span of sawi working in one bagang. If high-trust is created, the sawi will stay in one bagang for a long time. However, if there is low-trust, the sawi will choose to move to another bagang. Trust is essential in this working relationship and determines the length of cooperation between punggawa and sawi.